Marijuana (Cannabis): It’s Illusion And Information - SAHA RAJSEKHAR (International Journal of Pharma and Bio Sciences, 2012)
The present article deals with the pharmacognosy, pharmacology and many other aspects about the plant marijuana that is well known as cannabis. The above plant has been through many legal and medical issues all round the world. The use of this plant in medical purposes has been a long time hot topic in our fraternity. The plant has been blamed to have an addiction causing character. On the other hand, It has also been supported to have a good and accepted pharmacological activity by literature and practical users. Marijuana was first used for medical purpose in Britain in the mid-nineteenth century by O’Shaughnessy, a surgeon in army. In India the above plant has been used in wide range of medical condition such as rabies, epilepsy, muscle spasms and for pain relief. This article is a sincere effort to bring forward the possible information about the plant, its chemical constituents and uses. The plant has been in talk for long time regarding the use and legal aspect and so detailed information regarding it should be necessary.